BAHASA TUBUH DALAM KARYA SENI PATUNG REALISME - BENO BANIANTO, Dra. Lisa Widiarti, M.Sn., Drs. Erfahmi, M.Sn. (Serupa The Journal of Art Education, 2018)
the purpose of creating works of art is to know the extent to which body language plays a role in human social life as the delivery of nonverbal messages, and to present works of sculptures that look at body pieces and visualize works by using a realist style. Method of cultivating results in the idea of art ideas in the creation process are among others: Preparation, elaboration, synthesis, concept realization, and completion. The results of the process through the idea into the form of sketches designed in such a way Based on the photographs made sketches which then consulted to the supervisor when it was getting the concept of work then visualize it in the form of a realist sculpture. the final stage of the process of making works where the author is ready to visualize into a final work as a condition for completing the degree program of art education.Keywords: Body Language, Statue, Realist.